KARAKTERISASI DAN UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN SERAI (Cymbopogon citratus) DESA BANDAR KHALIPAH TERHADAP MENCIT JANTAN (Mus musculus) - Tambunan, Pravil Mistryanto (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
Research has been carried out to determine the LD50 value and observe the toxic effects of Ethanol Extract of Lemongrass Leaves (EEEL) on male mouse using 64 male mouse which were divided into 4 groups. The control group was given 0.5% CMC-Na suspension while the treatment group was given a single dose of EEEL suspension with doses of 1500, 3500, and 7000 mg/kg BW given on the first day. Observations of toxic symptoms, changes in body weight and number of deaths were carried out for a span of 7-14 days. After observation, the surviving mouses were sacrificed for macropathological and histopathological examination of the liver and kidneys. The determination of the LD50 value was calculated based on the Indonesian Pharmacopoeia Method Edition VI, while the statistical data was tested using Quadratic Nonlinear Regression (QNR) with the SPSS computer program. The simplicia characterization showed positive results on triterpenoid, tannin, flavonoid, and saponin tests, and anthraquinone glycosides and negative results on alkaloid and steroid tests. The results showed that there were toxic symptoms starting in the 3500 and 7000 mg/kg BW dose groups. The statistical results of Quadratic Nonlinear Regression (QNR) also showed no significant difference between each group. In addition, there were no color differences in all groups in the results of organ macropathology. However, liver damage was found on organ macropathological examination at doses of 1500, 3500, and 7000 mg/kg BW. Meanwhile, EEEL doses of 3500 and 7000 mg/kg caused glomerular hypertrophy and dilation of several renal tubules. The LD50 result is 4,965.92 mg/kg BW which indicates that EEEL was categorized as moderate toxic.